ENVIRONMENTAL PLANNING OF ABANDONED QUARRIES REHABILITATION – A METHODOLOGY - Hagiou, Eleonora; Konstantopoulou, Garyfalia (Bulletin of the Geological Society of Greece, 2010)
Restoration of abandoned quarry sites has been for quite a few years practiced in various places in Greece, mainly in the broader district of Athens, a wide range of rehabilitation solutions has been used by the local authorities in order to cover basic needs of the population (cultural and athletic centres, municipal storage and parking facilities for heavy vehicles, open theatres, municipal waste facilities, cemeteries etc.). Still restoration of abandoned quarries (aggregate material, marble, industrial minerals etc) remains a major problem for almost every prefecture and has to be solved gradually due to lack of the necessary funds, solving the most acute environmental problems and covering basic needs of the population for municipal facilities. In this paper the development of a methodology is presented for the elaboration of a priority list for the restoration/rehabilitation of numerous abandoned quarries comprised in a geographical or administrative entity. Using multi-criteria analysis and geographical information system we have concluded in a quick and cost effective method for the hierarchical classification of restoration sites. The establishment of an adequate set of criteria for the priority list is of main importance for the successful application of the method.